S=5+2J
S+J=17
s-2J=5
s+J=17
subtract first equation from second
3J=12
J=4
Sam's age is five years more than twice Jessica's age. Together, the sum of their ages is 17. Let J = Jessica's age?
3 answers
"Sam's age is five years more than twice Jessica's age."
So, Sam's age, which I will designate a "s" is 5 years more than twice Jessica's age, which I will designate as "j".
From this we can realize that twice Jessica's age (2j) plus 5 is equal to Sam's age. From this, we can get the equation:
s = 2j + 5
"Together, the sum of their ages is 17."
This one's pretty straightforward:
s + j = 17
So now we have the system of equations:
s = 2j + 5
s + j = 17
Since we know that s = 2j + 5, we can substitute 2j + 5 for s in the second equation:
s + j = 17
(2j + 5) + j = 17
By using algebra to solve for J in the equation above, you will arrive at the correct answer.
So, Sam's age, which I will designate a "s" is 5 years more than twice Jessica's age, which I will designate as "j".
From this we can realize that twice Jessica's age (2j) plus 5 is equal to Sam's age. From this, we can get the equation:
s = 2j + 5
"Together, the sum of their ages is 17."
This one's pretty straightforward:
s + j = 17
So now we have the system of equations:
s = 2j + 5
s + j = 17
Since we know that s = 2j + 5, we can substitute 2j + 5 for s in the second equation:
s + j = 17
(2j + 5) + j = 17
By using algebra to solve for J in the equation above, you will arrive at the correct answer.
I don't get how i still get the answer